Long lasting octreotide LAR therapy in non functioning pancreatic neuroendocrine carcinoma - Ivan Lolli; Antonio Logroscino; Simona Vallarelli; Maria A. Monteduro; Antonella Gentile; Giuseppe Troccoli (Clinical Management Issues, 2015)
Non functioning endocrine pancreatic tumors (NF-PETs) have absent or low hormone secretion without symptoms and constitue ~60% of PETs. At diagnosis more than 50% of patients have liver metastases and almost 40% are not candidates for radical surgery because of either locally advanced disease or unresectable metastases. We described the case of a 47-year-old woman with a pancreatic carcinoma with secondarism in the liver not suitable for radical surgery. Histological test of liver metastases showed positivity for endocrine well-differentiated non functioning carcinoma expressing receptors for somatostatin with very low proliferation index (Ki67 < 2%). After this diagnosis she started a specific treatment with octreotide analogues which achieved durable stabilization of the disease.